Blood pressure and renal function in autosomal dominant polycystic kidney disease - Seeman, T; Sikut, M; Konrad, M; Vondrichová, H; Janda, J; Schärer, K (Pediatric nephrology (Berlin, Germany), 1997)
The purpose of this study was to identify hypertension in children and adolescents in an early stage of autosomal dominant polycystic kidney disease (ADPKD) by the application of ambulatory blood pressure monitoring (ABPM) over 24 h; 32 children and adolescents (mean age 12.3 +/- 4.7 years) were examined. The diagnosis was based on family history and ultrasound examination. In 21 children ADPKD was confirmed by molecular genetic analysis. At the time of the study, 45% patients were asymptomatic and all had glomerular filtration rates (GFRs) > or = 65 ml/min per 1.73 m2. By ABPM, 11 patients (34%) were defined as hypertensive (systolic or diastolic blood pressure > 95th percentile), including 4 with an exclusive nocturnal hypertension. Of 7 patients with daytime hypertension, 4 had normal blood pressure by casual measurements. The nocturnal dip in blood pressure was reduced in 2 patients. Blood pressure correlated with renal size, but not with GFR, concentrating capacity, proteinuria, and plasma renin activity. The study reveals an early trend for increased blood pressure in children with ADPKD, requiring close supervision.
Keywords: Humans; Polycystic Kidney, Autosomal Dominant; dítě; polycystické ledviny autozomálně dominantní; Child; ledviny; Glomerular Filtration Rate; Female; dospělí; Kidney; Ultrasonography; lidé; Blood Pressure Monitoring, Ambulatory; ambulantní monitorování krevního tlaku; hodnoty glomerulární filtrace; Adult; ultrasonografie; ženské pohlaví; krevní tlak; Male; Adolescent; mužské pohlaví; Blood Pressure; mladiství